Avaliação e gerenciamento de resíduos de impacto ambiental provenientes de equinos estabulados - Lagomarsino, Mariana Medeiros (2019)
This paper aims to analyze if the farms with intensive horse breeding in Rio Grande do Sul perform the correct management of the residues produced by the activity. Through this, we seek to understand the procedures adopted regarding the storage, treatment and reuse, when applicable, and the final destination of agricultural residues and Health Services Waste, as well as the level of knowledge of equinoculturers about subject matter. For this, a semistructured interview was applied to the producers, which is divided into four stages. The first and second encompassed general questions regarding zootechnical production data. The third part comprised zootechnical data of environmental sanitation seeking to understand the zootechnical management adopted by the interviewees. Finally, the last step included the management of waste produced. In total, 88 interviews were conducted. Part of the data has been tabulated in Microsoft Excel for better understanding and graph generation. A descriptive statistics and a descriptive analysis was performed to generate the results. The data collected showed that equinoculturists do not correctly manage the waste generated. Few properties perform the treatment of organic waste through composting. Nevertheless, most of these waste products are used as organic fertilizer. With regard to storage, most perform this step incorrectly for agricultural waste and for Health Services Waste, which in the latter case are also mostly misused. From the reality found proposals for adjustments in the waste management process were formulated.